Are conservation organizations configured for effective adaptation to global change?. Issue 3 (1st April 2015) - Armsworth, Paul R; Larson, Eric R; Jackson, Stephen T; Sax, Dov F; Simonin, Paul; Blossey, Bernd; Green, Nancy; Klein, Mary L; Lester, Liza; Ricketts, Taylor H; Runge, Michael C; Shaw, M Rebecca
Abstract : Conservation organizations must adapt to respond to the ecological impacts of global change. Numerous changes to conservation actions (eg facilitated ecological transitions, managed relocations, or increased corridor development) have been recommended, but some institutional restructuring within organizations may also be needed. Here we discuss the capacity of conservation organizations to adapt to changing environmental conditions, focusing primarily on public agencies and nonprofits active in land protection and management in the US. After first reviewing how these organizations anticipate and detect impacts affecting target species and ecosystems, we then discuss whether they are sufficiently flexible to prepare and respond by reallocating funding, staff, or other resources. We raise new hypotheses about how the configuration of different organizations enables them to protect particular conservation targets and manage for particular biophysical changes that require coordinated management actions over different spatial and temporal scales. Finally, we provide a discussion resource to help conservation organizations assess their capacity to adapt.